LAYANAN BIMBINGAN DAN KONSELING ISLAM DALAM PEMENUHAN KESEHATAN MENTAL BAGI ANAK KORBAN KEKERASAN DI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KABUPATEN GOWA - Syamsidar Syamsidar; Walidah Walidah (240-540X)
Islamic guidance and counseling is very necessary for child victims of violence because of guidance and counseling. Guidance and counseling services also play an important role in the mental health recovery process carried out by P2TP2A, Gowa Regency. This is important to be done in the context of recovering trauma for a child who is experiencing violence.